Hubungan Tingkat Pengetahuan Tentang Anemia dengan Tindakan Pencegahan Anemia untuk Persiapan Kehamilan pada Pasangan Usia Subur - Aminingsih, Sri; Putra, Alfinda Choirul (KOSALA : Jurnal Ilmu Kesehatan, 2019)
Background: According to Fuady and Bangun's research (2013) iron deficiency anemia in pregnancy is the condition of mothers with hemoglobin levels below 11 gr% in the first and third trimesters or hemoglobin levels <10.5 gr% in the second trimester and is one of the causes of death in pregnant women . In Indonesia the prevalence of pregnancy anemia is relatively high, which is 38% - 71.5% with an average of 63.5%. The results of the analysis in this study knowledge affect the adherence of respondents with p = 0.011 (p <0.05). From the initial survey in Slogoretno Jatisrono Wonogiri Village conducted by researcher in 3 couples of childbearing age, only 1 mother had enough knowledge about anemia. The purpose: Describing the relationship between Knowledge Level About Anemia with Prevention Anemia for pregnancy preparation in couples of childbearing age. The research is analytic with correlation design, this study aimed to analyze the relationship of knowledge about anemia as the independent variable and anemia prevention for pregnancy preparation as the dependent variable with the number of respondents 55 people. The results of the study using the Chi-Square Correlation Test obtained p at 0,000 Results: Couples of childbearing age with high knowledge level were 40 respondents (72.73%), while those with low knowledge level were 15 respondents (27.27%). Prevent anemia performed optimally by couples of childbearing age were 28 respondents (50.91%) while anemia prevention measures were less than 27 respondents (49.09%). The Conclusion: There is a relationship between knowledge level about anemia with anemia prevention for preparation of pregnancy in couples of childbearing age. Keywords: Knowledge about anemia, anemia prevention